Electrochemical Degradation of Remazol Black B Using Carbon Electrode - Muh. Supwatul Hakim; Stevin Carolius Angga; Mokhamat Ariefin; Riandy Putra (Akta Kimia Indonesia, 2026)
The presence of dye waste in the environment can affect ecosystems and humans. Therefore, this study aims to degrade Remazol Black B dye waste, which has been widely used as a synthetic dye in the batik and textile industries. The electrochemical degradation of RBB waste has been successfully carried out using carbon electrodes from battery waste. The influence of voltage and electrolysis time, as well as decolorization efficiency, has also been analyzed using a UV-Vis spectrophotometer. Based on the results, the optimum voltage and time for RBB degradation were obtained at 15 volts for 20 minutes with an efficiency of 100%. Meanwhile, at voltages of 5 and 10 volts, the efficiencies were 70% for 60 minutes and 100% for 30 minutes, respectively. The use of carbon electrodes from battery waste offers a new alternative for easy and efficient color waste treatment.